EKSTRAK DAUN JATI MUDA UNTUK PEWARNA PEMERIKSAAN SEDIMEN URINE - Doni Setiawan; Atun Farihatun; Ary Nurmalasari; Euis Tia Istianah; Mujahidah Basarang; Ellies TS Maulidiyanti2 (Universitas Muhammadiyah Surabaya, 2024)
Urinalysis examination is needed to find information and determine the condition of the kidneys, urinary tract or other organs such as the liver, pancreas, and bile ducts. A urinary sediment examination aims to see organic and inorganic elements in the urine by preparing using Sternheimer Malbin stain reagents. Sternheimer Malbin stain has the disadvantage that it is a synthetic chemical. Stain from natural ingredients becomes a solution as an alternative to reduce the use of synthetic chemicals. Natural stains with the same characteristics and widely tested for bacterial and fungal stains are natural stains from teak leaf extract. Young leaf extract contains anthocyanins in red colour. This study aimed to determine the ability of ethanol extract from young leaves as a natural stain for urine sediment examination. The research method is an experiment with the Static Group Comparison research design. The population and samples in this study are teak leaves determined at the Galuh University Laboratory of the Biology Study Program with the Latin name (Tectona grandis L.f.). The results of the Fisher Exact test obtained a p (value) <0.050, so there was no significant difference between sediments without stain, Sternheimer Malbin, and ethanol extract of young leaves in colouring urine sediments. The conclusion is that the dye of ethanol extract from young teak leaves effectively colours the components of urine sediment, namely epithelial cells, leukocyte cells, and erythrocyte cells with red colour. Keywords : Anthocyanins, Alternative Dyes, Sternheimer malbin